Evaluasi Efektivitas Sistem Akademik Menggunakan Model Servqual Untuk Meningkatkan Kualitas Layanan - Jerry Wahyu Hidayat; Monsya Juansen; Kirman Kirman; Surya Ade Saputera (Jurnal Media Infotama, 2024)
Academic Information System is a computer-based system built with the hope of academic interests which aims to increase the quality of academic services, performance and human resources, as well as the resulting competitiveness. The Academic information system makes it easy for students to access important information related to the University such as course lists, grades, administration, academic calendars, information about each department and others. With the development of information systems in the academic field, it is also necessary to test information systems to find out whether the development and objectives of the information system are as expected. The purpose of this research is to determine the level of student satisfaction with the quality of academic information system services (SIKAMU) using The ServQual method provides recommendations for which variables need improvement in improving the quality of SIKAMU academic information system services. The research method used in this research is e-service quality or what is called e-servqual. From the research results, it was found that the gap or gap between expectations and reality is not too big, which means that the quality of the academic information system in the SIKAMU application is good, only a few small aspects need to be improved. Furthermore, from the aspect of student satisfaction, it can be concluded that Bengkulu Muhammadiyah University students are satisfied with the services provided by the SIKAMU information system. With an average overall rating of 80% (satisfied). This means that students' expectations regarding the five dimensions of service have been fulfilled even though they are not very in line with what students expected